A deeper understanding of depression and suicidality among medical students. (3rd June 2019) - Heiman, Noa; Davis, Rachel; Rothberg, Brian
Abstract: Prevalence rates for depression among medical students are three times higher than the prevalence rates of depression in the general population. In order to understand these high prevalence rates, the authors discuss the underlying psychodynamics of a subset of medical students who seek therapy for depression and suicidality during their medical school years. Does medical school screen for people who are more prone to depression or does medical school cause high depression rates? The authors describe students with the combination of harsh/critical aspects from their early family life coupled with emotional misattunement of caregivers. The authors then discuss how the medical school environment may lead to reeexperiencing of these dynamics, triggering depression and suicidal ideation. The article provides recommendations for identifying these students and referring them to mental health services.